The Effectiveness of Edutainment toward Pregnancy Care on Knowledge, Attitude, and Action in Pregnant Women - Firdausia, Shalsabilla Tiara; Budihastuti, Uki Retno; Dewi, Yulia Lanti Retno (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Playing or studying in a plea